2015
DOI: 10.5483/bmbrep.2015.48.7.218
|View full text |Cite
|
Sign up to set email alerts
|

Cell type-specific gene expression profiling in brain tissue: comparison between TRAP, LCM and RNA-seq

Abstract: The brain is an organ that consists of various cell types. As our knowledge of the structure and function of the brain progresses, cell type-specific research is gaining importance. Together with advances in sequencing technology and bioinformatics, cell type-specific transcriptome studies are providing important insights into brain cell function. In this review, we discuss 3 different cell type-specific transcriptome analyses i.e., Laser Capture Microdissection (LCM), Translating Ribosome Affinity Purificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…For instance, Map1b gene expression was downregulated in AD temporal cortex [123], whereas downregulation of Synpo protein in dendritic spines occurred in frontal cortex neurons in AD [9] similar to that found in our LC gene array experiments. Future studies employing single population RNA-sequencing, Fluidigm, and/or Nanostring nCounter analyses are warranted when transcriptomic technologies become more standardized and economical [22, 66, 73]. …”
Section: Resultsmentioning
confidence: 99%
“…For instance, Map1b gene expression was downregulated in AD temporal cortex [123], whereas downregulation of Synpo protein in dendritic spines occurred in frontal cortex neurons in AD [9] similar to that found in our LC gene array experiments. Future studies employing single population RNA-sequencing, Fluidigm, and/or Nanostring nCounter analyses are warranted when transcriptomic technologies become more standardized and economical [22, 66, 73]. …”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the upregulation of neuronal Chrna7 during AD has been reported by both in situ hybridization and immunohistochemical approaches (Counts et al, 2007; Hellström-Lindahl et al, 1999; Teaktong et al, 2004). Future studies employing single population RNA-sequencing, Fluidigm, and/or Nanostring nCounter analyses are warranted when single population transcriptomic technologies become more standardized and economical (Buettner et al, 2015; Kim et al, 2015; Macosko et al, 2015) for human postmortem tissue use.…”
Section: Resultsmentioning
confidence: 99%
“…This leaves a significant fraction of genes whose parent of origin cannot be defined in this particular cross (see Supplemental Figure 4 for analysis of accession combinations providing additional coverage). Despite this limitation, the ease of experimental setup and noninvasive nature of the technique argue for this approach, which does not require the extensive postharvesting purification steps required for alternative biochemical approaches such as TRAP-seq (Lin et al, 2014;Kim et al, 2015) or isolation of nuclei tagged in specific cell types (INTACT; Deal and Henikoff, 2011). Our analysis of Cvi x Col cross-pollinations revealed that ;8% of pollinated A. thaliana pistil RNA is derived from the pollen tube and we found strong correlations between our analysis and previous microarray analyses of the component cell types (microarray experiments recently reviewed in Rutley and Twell [2015]; Figure 2).…”
Section: Discussionmentioning
confidence: 99%